Nudging International Sustainable Practices Confirmed with Renewable Energy Consumption - Gupta, Suman (International Journal of Energy Economics and Policy, 2023)
The study explores the resemblance of the countries based on renewable energy consumption (% of total energy consumption). A simplistic clustering approach is applied to implement the segmentation using the gap statistic method. The paper deals with the comparability of countries from the perspective of income level and geographical distribution. The clustering-based results reveal that the values of most mean clusters representing major economies have deteriorated over the past few years. The High and Upper-middle income countries are found to be not following sustainable practices, while Low and Lower-middle income countries are relying much on renewable energy consumption. The outcome is also presented as clusters for geographical distribution and a cross-section distribution of Income level-Region for all economies sampled. The study may assist in policy-making in the wake of the global clean energy transition.